Good Governance in Public-Private Partnerships : A Resource Guide for Practitioners - World Bank (Washington, DC, 2013)
Public-Private Partnerships (PPPs) provide a new 'model' for infrastructure service delivery, which combines elements borrowed from other legal economic and financial structures. A mixture of elements derived from public procurement, project finance, concession contracts, and policy network theories provides the background for PPPs structures. PPPs not only articulate such elements in one product but also constitute separate evolutions of the structures they originate from. In part, PPPs have been created to solve some problems those domains have generated or were not able to solve efficiently. However, PPPs are not meant to replace those domains but to provide alternative options to them. The natures of PPPs are associated with a new contract, procurement and relationship type. For some, a PPP is a new 'contract type' whose main characteristics are risk sharing between the public and private party; bundling of construction and operation; output base specifications; and long term commitments serve to define and distinguish the type others PPPs as a 'procurement type', alternative to traditional public procurement (including outsourcing), and concession. For some others, PPPs constitute new 'relationship types' between the Public Administration (PA), private parties and stakeholders involved in an infrastructure service delivery project. Indeed, a PPP is all of the above: a new contract, procurement, and relationship type. The origin of these typological diversities is mainly due to the different perspective legislators, practitioners, and scholars have had toward PPPs.